SYNTHESIS AND STATISTICAL STUDY OF MULTI WALL CARBONNANOTUBES ON Cu SUBSTRATE USING ELECTROCHEMICALCELL - RASHEED, ABDUL-JABBAR; HUSSAIN, DHIA; KHALAF, HUDA (Iraqi Journal of Science, 2024)
Multi wall carbon nanotubes (MWCNTs) were grown directly on coppersubstrate and in the acetonitrile / de-ionized water (1% v/v) electrolyte of theelectrochemical cell using different growth temperatures.The effects of substratetemperature and growth time over the MWCNTs structure were investigated.MWCNTs were characterized by Scanning Electron Microscopy (SEM), LowMagnification Transmission Electron Microscopy (LMTEM) and Atomic ForceMicroscopy (AFM). TEM characterization indicate a transition from non growth at288K to negligible growth at 308K then to excellent growth at 338K, AFMcharacterization indicate a Gaussian distribution growth on Cu substrate withmaximum percentage to 110 nm diameter.